The role of the secondary school in preparing youth for self - employment - Amarasinghe, V.R. (My University, 1984)
The purpose of this study i s to examine the nature of the role of the secondary school in preparing yonth for self-employment. The socio-economic conditions of the country indicate that self-employment plays a significant role in the country and i t s economy. Hence one would expect the secondary school to develop knowledge, attitudes and skills in youth pertaining to this fieldo The first chapter explains the nature and changing pattern of yotjth development. The problem is viewed in the light of the early maturity of youth, the structure of the secondary school and different views held of what is expected of the secondary schoolo It also gives the need for this study, i t s delimitation and objectiveso The second chapter illustrates the different patterns of vocationalization of secondary education in a number of « countries with a view to link the secondary school with the world of work. Chapter three i s an attempt to trace the history of education in the country in relation to the world of work. An analysis of the traditional learning system and employmenl profile is followed by a historical study of attempts in curricular diversification in secondary education* Chapter four includes an examination of the junior secondary school curriculum in relation to development of skills much needed for self-employment. Here the objectives, content and methodology of a wide array of subjects i s being examined with the objective of finding out whether they help in the development of s k i l l s for selfemployment. Chapter five conveys the practical approach to the study. It illustrates the design of the investigation and how i t i s implemented. The survey includes three samples. The first sample includes nine hundred secondary school students from three educational districts. The second sample consists of one hundred youth in self-employment (fifty pavement hawkers and f i f t y others employed as grocery shop owners, textile dealers, sewing g i r l s , glassware and fancy goods owners and book shop owners. The third sample includes fifty youths in selfemployment , in the fields of Carpentry, Agriculture, Fisheries Masonry and Mechanical work. The findings from these three samples are analysed in this chapter. The results thus collected have been interpreted and the researcher's conclusions given in chapter six. A number of extraneous factors which seem to exert tremendous influence in developing s k i l l s , abilities, understandings, attitudes, work habits and self-reliance in youth have been described. The final chapter refers to the limitations of the study and possibilities for further research in the allied f i e l d . The concluding paragraphs of this chapter embody suggestions for implementation.